2002
DOI: 10.1046/j.1365-201x.2002.01029.x
|View full text |Cite
|
Sign up to set email alerts
|

Altered sarcoplasmic reticulum function in rat diaphragm after high‐intensity exercise

Abstract: The present study examined the effects of acute high-intensity exercise on Ca(2+) uptake and release rates and Ca(2+)-adenosine triphosphatase (ATPase) activity of the sarcoplasmic reticulum (SR) from the costal diaphragm. The rats were run on a treadmill at an estimated requirement of 100% of maximal O2 consumption until fatigued (average time to exhaustion: 4.79 min). Muscle lactate and inorganic phosphate after exercise were increased by 65% (P < 0.05) and 35% (P < 0.05), respectively. With exercise, Ca(2+)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2003
2003
2007
2007

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 25 publications
1
6
0
Order By: Relevance
“…It is possible, given the apparent increased SR membrane permeability, that the decrease in Ca 2ϩ uptake that we observed in SOL and RG with the contractile activity in this study could have been even more pronounced if a Ca 2ϩ leak through the membrane was present. Previous studies using different exercise protocols have not reported any changes in the ionophore ratio in SOL (54), red vastus/RG (5), or diaphragm (34).…”
Section: Discussionmentioning
confidence: 96%
“…It is possible, given the apparent increased SR membrane permeability, that the decrease in Ca 2ϩ uptake that we observed in SOL and RG with the contractile activity in this study could have been even more pronounced if a Ca 2ϩ leak through the membrane was present. Previous studies using different exercise protocols have not reported any changes in the ionophore ratio in SOL (54), red vastus/RG (5), or diaphragm (34).…”
Section: Discussionmentioning
confidence: 96%
“…The different musclespecific responses are related to the oxidative potential of the muscle (13) and may reflect differences in second messenger regulation of SERCAs and/or redox homeostasis. Similarly, in response to different types of exercise, SR Ca 2ϩ uptake measured in rat diaphragm homogenates is either increased (43) or decreased (23), which may reflect differences in ROS production and/or second messenger activation, depending on the exercise protocol employed.…”
Section: Discussionmentioning
confidence: 99%
“…SR Ca 2+ uptake rate was measured by using the fluorescent dye indo-1 as previously described in detail [23,25]. The assay mixture (pH 7.0) consisted of (in mM) 100 KCl, 20 HEPES, 6.8 K-oxalate, 10 Na-azide, 1 M indo-1, 0.5 MgCl 2 and 2 M free Ca 2+ .…”
Section: Ca2+ Uptake Measurementsmentioning
confidence: 99%